THE STRATEGY OF COFFEE CUSTOMER SATISFACTION IMPROVMENT THROUGH ATMOSPHERE STORE, DISCOUNTS AND SERVICE QUALITY - Imamah, Nurul; Nur Iradawaty, Sofiah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
Advances in scientific knowledge and technology on a high scale, changing the cultural, social, political and life structures of the world community so quickly, resulting in the emergence of demands for the fulfillment of increasing human needs and can change the circulating trend itself, also able to change lifestyles, perspectives , as well as a person's habits. One of the lightest habit changes is liking coffee drinks, both homemade and enjoying coffee in coffee shops. This study aims to analyze the increase in coffee customer satisfaction strategy through store atmosphere, discount and service quality approach at EbesQu Kofie & Eatery Malang. This research is a quantitative research using simple random sampling method and using multiple linear regression analysis techniques. The results of this study indicate that store atmosphere, service quality and discount simultaneously are strategies that can significantly increase coffee customer satisfaction at EbesQu Kofie & Eatery Malang. Store atmosphere and partial discounts can significantly increase coffee customer satisfaction at EbesQu Kofie & Eatery Malang. Where the quality of service cannot increase coffee customer satisfaction significantly at EbesQu Kofie & Eatery Malang. Meanwhile, the independent variable that has the dominant influence on increasing coffee customer satisfaction at EbesQu Kofie & Eatery Malang is the store atmosphere.